Solidago graminifolia (L.) Elliott on anthropogenic sites of the Silesian Upland (Poland) - Kompała-Bąba, Agnieszka; Bąba, Wojciech (Biodiversity: Research and Conservation, 2006)
The aim of this paper is to show the distribution of Solidago graminifolia (L.) Elliott in the Silesian Upland and to examine the floristic composition of phytocoenoses with its participation. This species was recorded on anthropogenic habitats such as: open-cast quarry, railway embankment and ditches. The floristic diversity of phytocoenoses can be explained by two environmental gradients: soil fertility (marked on I PCA axis) and moisture and soil reaction (marked on II PCA axis). Phytocoenoses which develop in the open-cast quarry are the richest in species and the most differentiated. In their floristic composition meadow species (particularly from the Molinetalia order) occurred with high frequency. Phytocoenoses which grow in wet places, with a high ground water level, are distinguished by species from the Scheuchzerio-Caricetea fuscae and Phragmitetea classes, whereas in those which are confined to drier places short-lived species from the Stellarietea mediae class can be found.